Pulse Effect of Precipitation: Spatial Patterns and Mechanisms of Soil Carbon Emissions - Jiang, Zhaoxia; Bian, Hongfeng; Xu, Li; Li, Mingxu; He, Nianpeng (Frontiers in Ecology and Evolution, 2021)
The rapid and strong release of CO2 caused by precipitation (known as the pulse effect) is a common phenomenon that significantly affects ecosystem C cycling. However, the degree to which the pulse effect occurs overlarge regional scales remains unclear. In this study, we conducted continuous and high-frequency measurements of soil CO2 release rates (Rs) for 48 h after simulated precipitation, along a precipitation gradient of different grassland types (i.e., meadow, typical, and desert) in Inner Mongolia, China. Pulse effects were assessed using the maximum Rs (Rsoil–max) and accumulated CO2 emissions (ARs–soil). Strong precipitation pulse effects were found in all sites; however, the effects differed among grassland types. In addition, an apparent decrease in both Rsoil–max and ARs–soil was observed from the east to west, i.e., along the decreasing precipitation gradient. ARs–soil values followed the order: temperate meadow grassland (0.097 mg C g–1 soil) > typical temperate grassland (0.081 mg C g–1 soil) > temperate desert grassland (0.040 mg C g–1 soil). Furthermore, Rsoil–max and ARs–soil were significantly positively correlated with soil quality (SOC, POC, and N, etc.; P < 0.01). ARs–soil (P < 0.05) and ARs–SOC (P < 0.01) were significantly affected. ARs–soil and ARs–SOC were also positively correlated with soil microbial biomass significantly (P < 0.05). Rsoil–max and ARs–soil had similar spatial variations and controlling mechanisms. These results greatly support the substrate supply hypothesis for the effects of precipitation pulses, and provide valuable information for predicting CO2 emissions. Our findings also verified the significant effect of soil CO2 release from precipitation pulses on the grasslands of arid and semi-arid regions. Our data provide a scientific basis for model simulations to better predict the responses of ecosystem carbon cycles in arid and semi-arid regions under predicted climate change scenarios.